On the wings of Icarus – the need for transcendence in addictive diseases - Unterrainer, Human-Friedrich (Frontiers in Psychiatry, 2025)
This essay employs the Icarus myth as a metaphor to examine the role of transcendence in addiction. Icarus’ disregard for boundaries, driven by his quest for transcendence, mirrors the behavior of individuals with addictive tendencies. Addiction, a chronic disorder marked by compulsive substance use or behaviors, is characterized by loss of control, tolerance, withdrawal, and life disruptions. Furthermore it is linked to traits such as impulsivity and sensation-seeking. Transcendence, the pursuit of experiences beyond ordinary limits, often manifests in addiction as a distorted attempt to address spiritual or existential voids. While practices like meditation can facilitate healthy transcendence (e.g., by influencing the periaqueductal grey activity), addiction provides only fleeting euphoria, perpetuating dependency. Sigmund Freud’s concept of “oceanic feelings” (discussed in correspondence with Romain Rolland) and Abraham Maslow’s notion of “peak experiences” parallel the addict’s pursuit of unity and self-actualization. However, addiction undermines genuine fulfillment and growth. Spirituality emerges as a pivotal factor in both the development and recovery of addiction, offering reconnection to meaning, purpose, and a higher power. Neuroscientific insights suggest ancient brain regions, such as the Periaqueductal Grey, may underlie the human drive for transcendence. Drawing on Jungian psychology, the essay highlights spirituality’s role in addressing existential crises and guiding recovery, echoing Jung’s “Spiritus contra Spiritum” as a principle for overcoming addiction. In conclusion, the essay advocates for a balanced approach in addiction therapy, harmonizing the innate human desire for transcendence with sustainable personal growth, and avoiding the extremes symbolized by Icarus’ fatal pursuit.